2013
DOI: 10.4103/2277-9175.122520
|View full text |Cite
|
Sign up to set email alerts
|

Topical nicotinamide in combination with calcipotriol for the treatment of mild to moderate psoriasis: A double-blind, randomized, comparative study

Abstract: Background:Current treatment strategies of psoriasis are not completely satisfactorily. By inhibiting inflammatory cytokines, nicotinamide may enhance the effects of current topical treatments. We investigated whether the combination of topical calcipotriol and nicotinamide is more effective than calcipotriol alone in treatment of psoriasis.Materials and Methods:Adult patients with mild to moderate psoriasis were randomized to receive topical calcipotriol 0.005% and nicotinamide 4% in combination or calcipotri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…This has been also confirmed by the Medical Investigator who considered that for nearly all patients, DENI gel was a helpful and convenient addition to their treatment regime. These observations are in line with published studies attesting to the effectiveness of topically applied nicotinamide in inflammatory skin conditions including AE and psoriasis 1518. The limitation of the study is that patients received samples labelled, but unblinded, as they would normally do in real-life settings when they get their emollient product(s) on prescription.…”
Section: Discussionsupporting
confidence: 83%
“…This has been also confirmed by the Medical Investigator who considered that for nearly all patients, DENI gel was a helpful and convenient addition to their treatment regime. These observations are in line with published studies attesting to the effectiveness of topically applied nicotinamide in inflammatory skin conditions including AE and psoriasis 1518. The limitation of the study is that patients received samples labelled, but unblinded, as they would normally do in real-life settings when they get their emollient product(s) on prescription.…”
Section: Discussionsupporting
confidence: 83%
“…Nicotinamide has been widely used to treat diseases such as diabetes, schizophrenia, Alzheimer's disease, psoriasis, obesity, and cancer (Aisen et al., 2008, Bagcchi, 2015, Chase et al., 1992, Chen et al., 2015, Gale, 2004, Knip et al., 2000, Siadat et al., 2013, Smythies, 1973). High dosage of nicotinamide is often required in clinical treatment, and the concentration in serum could reach the millimolar range (Dragovic et al., 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Viceversa, a previous in vitro study demonstrated that total NAD content is significantly increased by about 30% in both subcorneal and basal epidermal layers of psoriatic skin lesions, compared to uninvolved or healthy skin biopsies [32]. Although previous studies showed that the combination of NAM with calcipotriene may provide additional benefit in the topical treatment for patients with psoriasis [33,34], the effective efficacy of NAM in psoriasis management remains to be established.…”
Section: Introductionmentioning
confidence: 99%